A remote monitoring approach for coastal engineering projects - C. Cabezas-Rabadán; J. E. Pardo-Pascual; J. Palomar-Vázquez; A. Cooper (Scientific Reports)
Abstract High costs and project-based (short-term) financing mean that coastal engineering projects are often undertaken in the absence of appropriate post-construction monitoring programmes. Consequently, the performance of shoreline-stabilizing structures or beach nourishments cannot be properly quantified. Given the high value of beaches and the increase in erosion problems and coastal engineering responses, managers require as much accurate data as possible to support efficient decision-making. This work presents a methodological approach to characterise coastline position changes as a result of engineering actions. We describe a new, low-cost method based on satellite remote sensing to monitor shoreline evolution at high temporal and spatial resolution pre-, during and post-implementation. Initially, satellite-derived waterlines are identified and extracted from publicly available satellite imagery of the Landsat 5, 7, 8, and 9, and Sentinel-2 constellations using the automatic shoreline extraction tool SHOREX. The waterline positions are then compiled, differences over time are quantified, and a matrix is constructed that allows easy depiction and interpretation of spatial and temporal patterns of erosion/accretion. This allows the access and the comprehension of the morphological data by the non-expert. Two examples of application on the Valencian coast of Spain at different spatial scales demonstrate how beach response to coastal engineering actions can be characterised at different levels of detail (from local to regional) and over different periods of time. These applications evidence the utility of the approach as it allows analysis of pre- and post-intervention coastal change and offers a means to overcome the widespread lack of monitoring and hence to improve coastal engineering practice.